(untitled) (Palíndromo, 2021)
Visual essay that uses iconic elements of a flight routine taking the portrait as a category image This text presents the central points of the development of the Works of the series which compose the artistical project “Re[Di]ssonances”. By expatiate on this proposition, we present the visions on solitude registered by some exponents of philosophy and literature, which are related to the scope of the artistic production in question. By exploring the possibilities of expression of the most subjective livingness, we discuss the relation of the artistic practice with the desire on express the primordial aspects pertinent to the role of solitude in existence and the paradoxes which it contains.